The Influence Of Perceptions Of Taste And Promotion Through Instagram Social Media On Consumer Purchasing Decisions For Janji Jiwa Coffee Kedaton, Bandar Lampung - Herma Waty Simamora; Wenny Permata Sari (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to find out how consumers' decisions to buy Janji Jiwa Kedaton coffee in Bandar Lampung are influenced by taste perceptions and promotions using Instagram social media. The research sample consisted of 100 respondents, namely consumers who consumed Janji Jiwa coffee. Samples were obtained using a Liket scale. The quantitative descriptive approach applies a research design characterized by clearly defined objectives, methodology, participants, specimens, research procedures and data sources. With SPSS for Windows version 26, the data analysis method applies linear regression. After being investigated, the research findings show that 87% of consumers' decisions to buy Kopi Janji Jiwa Kedaton 100 are influenced by taste and promotions on Instagram, while the remaining 13% are influenced by other factors not included in the research. This research contributes that its findings should be applied as raw data for future research projects as well as a source of inspiration, validation, and introspection. This investigation shows that elements related to taste and promotion have a significant and beneficial impact on customer decisions regarding Janji Jiwa Kedaton coffee. To get people to come back to consuming Janji Jiwa coffee again, the company needs to make more efforts to improve the taste, monitor and update the menu, or add new menu items in addition to providing other attractive promotions. Customers tend to consume more when they realize the benefits of the product.